2018
DOI: 10.1016/j.envint.2018.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Low-level exposure to arsenic in drinking water and incidence rate of stroke: A cohort study in Denmark

Abstract: The results indicate that arsenic in drinking water even at low concentration is associated with higher incidence rate of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Furthermore, as it is difficult to convert plasma As to water As, we excluded two studies which could only provide plasma As concentration to lower the bias of exposure assessment [50,51]. In addition, as there was only one study analysing each of soluble E-selectin, myeloperoxidase, plasminogen activator inhibitor-1 (PAI-1), soluble Intercellular Adhesion Molecule 1 (ICAM-1) and soluble Vascular cell adhesion protein 1 (VCAM-1) [18], carotid atherosclerosis indices (CAIs) [52], common carotid intima media thickness, plaque score and the presence of plaque in the common carotid [53], peripheral vascular disease [54,55] as well as some other CVD subtypes and clinic markers [21,27,[56][57][58][59][60][61], respectively, these variables have not been included in our dose-response meta-analysis. Moreover, due to the fact that significant differences could be found regarding concentrations of matrix-metalloproteases (MMPs) using plasma vs. serum [62], we further excluded two studies which analysed the plasma MMPs and serum MMPs respectively to avoid bias in outcome ascertainment [18,21] ( Figure S1).…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as it is difficult to convert plasma As to water As, we excluded two studies which could only provide plasma As concentration to lower the bias of exposure assessment [50,51]. In addition, as there was only one study analysing each of soluble E-selectin, myeloperoxidase, plasminogen activator inhibitor-1 (PAI-1), soluble Intercellular Adhesion Molecule 1 (ICAM-1) and soluble Vascular cell adhesion protein 1 (VCAM-1) [18], carotid atherosclerosis indices (CAIs) [52], common carotid intima media thickness, plaque score and the presence of plaque in the common carotid [53], peripheral vascular disease [54,55] as well as some other CVD subtypes and clinic markers [21,27,[56][57][58][59][60][61], respectively, these variables have not been included in our dose-response meta-analysis. Moreover, due to the fact that significant differences could be found regarding concentrations of matrix-metalloproteases (MMPs) using plasma vs. serum [62], we further excluded two studies which analysed the plasma MMPs and serum MMPs respectively to avoid bias in outcome ascertainment [18,21] ( Figure S1).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Among all these studies, there were 13 cohort studies [15,17,19,20,26,29,63,71,[79][80][81][82], with one retrospective study [57], inferring causality between CVD endpoints and As exposure; six cross-sectional studies [59,[66][67][68]70,75]; five case-control studies [16,69,72,73,83]; one ecological study [74]; and three case-cohort studies [20,36,84].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in understanding the fate and behavior of As in various systems and improvement is the key. Perhaps something can be learnt from the drinking water utilities in New Jersey and Denmark where 5 μg/L As has been established as the maximum contaminant level since 2006 and 2017 respectively [18,19], as well as from The Netherlands where drinking water companies are making efforts to reduce As in drinking water to below 1 μg/L [20,21].…”
Section: The Way Forward?mentioning
confidence: 99%
“…The World Health Organization recognizes that at least 140 million people in 50 countries have been drinking water containing inorganic arsenic (iAs), a class 1 carcinogen, at levels above the recommended guideline value of 10 µg/L [1]. In some countries the maximum allowable level of iAs in drinking water has been reviewed, as different studies have found increased risk of disease development at concentrations below 10 µg/L [2,3] [4]. Recently, as a direct consequence of increased industrial activity and traffic pollution, the concentrations of iAs in polluted air (e.g.…”
Section: Introductionmentioning
confidence: 99%